GRADUATES' EVALUATIONS OF THE MASTER OF NURSING SCIENCE DEGREE PROGRAMME OFFERED BY THE UNIVERSITY OF BOTSWANA. - Sabone, M. B. (Africa Journal of Nursing & Midwifery, 2011)
The Master of Nursing Science (MNS) programme offered by the University of Botswana needed to be reviewed so that it could be synchronised with prevailing trends within the university, nationally, regionally, and internationally. The purpose of this customer satisfaction survey was to determine the extent to which these graduates' expectations had been met. The findings could provide ideas and inputs for reviewing this programme. The population comprised graduates for the period 1998-2007. A questionnaire with closed and open-ended questions was used to collect data. A convenience and snowball sampling method was employed. Descriptive statistics and content analysis methods were used to analyse quantitative and qualitative data respectively. Of the 53 respondents, 92.5% were females and 7.5% were males. These 53 returned the questionnaires, representing a response rate of 85.5%. Graduates were happy about the programme, but suggested some improvements. A summary of recommendations is presented, supported by relevant literature.